Microbial communities and volatile metabolites in different traditional fermentation starters used for Hong Qu glutinous rice wine. (July 2019) - Huang, Zi-Rui; Guo, Wei-Ling; Zhou, Wen-Bin; Li, Lu; Xu, Jia-Xin; Hong, Jia-Li; Liu, Hui-Peng; Zeng, Feng; Bai, Wei-Dong; Liu, Bin; Ni, Li; Rao, Ping-Fan; et al.
Abstract: Hong Qu glutinous rice wine (HQGRW), as one of the most typical representatives of Chinese rice wine, is generally brewed from glutinous rice by adding two traditional wine fermentation starters—Hong Qu (HQ) and Bai Qu (BQ). The objective of this study was to determine the microbial communities and volatile metabolites of different traditional fermentation starters for HQGRW, and elucidate the potential correlation between microbiota and volatile metabolites. Both heatmap and principal component analysis (PCA) revealed the significant variances in volatile profiles among different wine starters. Microbiological analysis based on high-throughput sequencing (HTS) technology demonstrated that both of bacterial and fungal communities varied significantly in different starters. HQ was dominated mainly by bacteria of Bacillus ginsengihumi (20.17%), Pantoea sp. (10.39%), Elizabethkingia sp. (5.52%), Streptococcus sp. (5.03%) Brevundimonas sp. (3.03%), Rickettsia prowazekii (2.94%), Thermus thermophilus (2.54%), Bacillus amyloliquefaciens (1.48%), Bacillus aryabhattai (1.42%); fungi of Monascus purpureus (39.7%), Aspergillus niger (27.35%), Xeromyces bisporus (8.39%), Aspergillus penicillioides (6.89%), Aspergillus flavus (2.33%) and Pichia farinose (0.79%). By contrast, BQ contained much higher proportions of bacteria of Lactococcus lactis (10.45%), Lactobacillus brevis (9.99%), Pediococcus pentosaceus (8.29%), Weissella paramesenteroides (6.69%), Lactobacillus fermentum (4.83%), Gluconobacter thailandicus (3.93%), Lactobacillus alimentarius (3.59%), fungi of Rhizopus arrhizus (31.47%), Saccharomycopsis fibuligera (27.86%), Aspergillus niger (20.81%), Issatchenkia orientalis (3.79%), Saccharomycopsis malanga (3.15%), Clavispora lusitaniae (2.29%), Candida tropicalis (1.47%), Saccharomyces cerevisiae (1.11%) and Rhizopus microsporus (0.57%). Furthermore, core functional microbiota that might contribute to volatile flavour development was explored through Spearman's correlation-based network analysis. Lactobacillus brevis, Lactobacillus alimentarius, Lactobacillus plantarum and Aspergillus niger were found to be strongly associated with acid compounds (FDR adjusted P < 0.01), while Pichia sp., Candida sp., Monascus purpureus, Lactobacillus brevis and Lactobacillus alimentarius were positively correlated with concentrations of aromatic esters associated with fruity and floral notes (FDR adjusted P < 0.01), implying that these microorganisms might make significant contributions to the flavour of rice wine. These findings demonstrated that the aromatic quality of HQGRW may be critically influenced by the microbiota in traditional fermentation starters. To conclude, this study would contribute to the development of novel defined starter cultures for improving the aromatic quality of HQGRW. Graphical abstract: Unlabelled Image Highlights: HQGRW is brewed with two traditional fermentation starters—Hong Qu (HQ) and Bai Qu (BQ). BQ was mainly dominated by L. lactis, L. brevis, R. arrhizus, and S. fibuligera . HQ was mainly dominated by B. ginsengihumi, Pantoea sp., M. purpureus, and A. niger . Microbial communities varied significantly in different traditional fermentation starters. L. brevis, L. alimentarius, R. microspores, and M. purpureus were related to volatile alcohols and esters.